The DsrD functional marker protein is an allosteric activator of the DsrAB dissimilatory sulfite reductase - Ferreira, Delfim (2022)
Funding Information: ACKNOWLEDGMENTS. We thank Christiane Dahl from the University of Bonn for critically reading the manuscript. This work was funded by the Fundac¸ão para a Ciência e Tecnologia (Portugal) through Fellowships PD/BD/135488/2018 (A.C.C.B.), PD/BD/128204/2016 (D.F.), and SFRH/BPD/79823/2011 (S.S.V.); Grants PTDC/BIA-MIC/6512/2014 and PTDC/BIA-BQM/29118/2017; and Research unit Molecular and Structural Microbiology (MOSTMICRO-ITQB) (Grants UIDB/04612/ 2020 and UIDP/04612/2020). The European Union’s Horizon 2020 Research and Innovation Program (Grant Agreement No. 810856) is also acknowledged. Publisher Copyright: © 2022 National Academy of Sciences. All rights reserved.